A Longitudinal Study of Parent-Child Interactions and Language Outcomes in Fragile X Syndrome and Other Neurodevelopmental Disorders - Bush, Lauren; Martin, Gary E.; Landau, Emily; Losh, Molly (Frontiers in Psychiatry, 2021)
Difficulties with pragmatic language (i.e., language in social contexts, such as conversational ability) are a noted characteristic of the language profiles of both fragile X syndrome (FXS) and autism spectrum disorder (ASD), conditions which show significant phenotypic overlap. Understanding the origins and developmental course of pragmatic language problems in FXS and other developmental conditions associated with language impairment is a critical step for the development of targeted interventions to promote communicative competence across the lifespan. This study examined pragmatic language in the context of parent-child interactions in school-age children with FXS (who did and did not meet ASD criteria on the ADOS; n=85), idiopathic ASD (n=32), Down syndrome (DS; n=38), and typical development (TD; n=39), and their parents. Parent-child communicative interactions were examined across multiple contexts, across groups, and in relationship to pragmatic language outcomes assessed two years later. Results showed both overlapping and divergent patterns across the FXS-ASD and idiopathic ASD child and parent groups, and also highlighted key differences in pragmatic profiles based on situational context, with more pragmatic language difficulties occurring for both ASD groups in less structured interactions. Differences in parental language styles during parent-child interactions were associated with child language outcomes, likely reflecting the complex interplay of discourse style inherent to a parent, with the inevitable influence of child characteristics on parent language as well. Together, findings help delineate the dynamic and multifactorial nature of impaired pragmatic skills among children with FXS and other neurodevelopmental disorders associated with language impairment, with potential implications for the development of targeted interventions for pragmatic communication skills.